EVALUASI PROGRAM PENGENDALIAN VEKTOR DBD DI PUSKESMAS MEDOKAN AYU KOTA SURABAYA TAHUN 2022 - Putri Sapphira, Nanda; Ngadino; Ernita Sari (Jurnal Higiene Sanitasi, 2022)
There were 111 cases of dengue fever in Surabaya in 2021 with the highest cases being at the Medokan Ayu Health Center with 13 cases. Based on data from the Medokan Ayu Health Center, there were 25 cases of dengue fever in 2021, and this increased to 28 cases from January to May 2022. The purpose of this study was to evaluate the implementation of the dengue vector control program at the Medokan Ayu Health Center, Surabaya City in 2022. The design of this research is descriptive and was conducted in April-July 2022. The total sample used was 22 people who had suffered from DHF in the working area of ​​the Medokan Ayu Public Health Center. The results of the interviews that have been conducted obtained 13 people with sufficient criteria and 9 people with good standart, those can be seen the implementation of the DHF vector control program at the Medokan Ayu Health Center is efficient. Of the 9 vector control activity variables, the Medokan Ayu Health Center only carried out 7 DHF vector control activities. The conclusion from the research that has been conduct is that the implementation of the dengue vector control program at the Medokan Ayu Health Center has been efficient. However, several variables scored less than the respondents, including counseling activities, eradicating mosquito nests, and fogging. Suggestions for Medokan Ayu Health Center and society to help each other in implementing the dengue vector control program.